Pengembangan Perangkat Pembelajaran IPA Berbasis Keterampilan Proses untuk Meningkatkan Keterampilan Berpikir Kritis Siswa SD: Development of Science Learning Tools Based on Process Skills to Improve Critical Thinking Skills for Elementary School Students - Yusuf, Mochamad (Pedagogia : Jurnal Pendidikan, 2018)
The purpose of this research is to develop a learning package for Sciences Subject that can improve the critical thinking skill of the Elementary School Students. Therefore, in general, it can be categorized into a research and development. It can be done because of learning material with process skill to practice it not available. The learning package was developed by using 4-D model; defining, designing, developing, distributing. The subject in this study was learning material that will be tested in student of SD Raden Patah Surabaya. The result showed that learning material was valid, enforceability get good category with 100%. Student activites by using process get good too. The improvement of students’ critical thinking is consistent on 3 classes (IVA, IVB, and IVC), the significant and high improvement with the average of N-Gain of 0,75. The data of students’ responses showed that most of students (98,09%) are happy to the process skill based learning. Based on the results and findings of the research, it can be concluded that the developed learning package can be stated as a valid, practical, and effective learning package. The implication of the research is that the process skill based Sciences learning can improve students’ critical thinking skill.